Based-Health Learning Management Site Study at SDN Magelang 6 Central Magelang - Rahayu, Wiwik Muji (2012)
This research has three objectives. Firstly is to describe characteristic of the implementation of based-health learning at SDN Magelang 6. Secondly is to describe characteristic of the role of School Health Center in the implementation of based health learning at SDN Magelang 6. It is a qualitative research which was done at SDN Magelang 6, Central Magelang. The informants of this research are the principal, teachers, and students of SDN Magelang 6, Central Magelang. Data collection technique used observation, interview, and documentation. Data analysis technique used analysis model such as data collection, data reduction, data display, and drawing conclusion. Data validity includes credibility, transferability, dependability, and confirmability. Based on the analysis, the write finds two results. First, the implementation of based-health learning at SDN Magelang 6 is applied on several subjects such as sport and health, and Science which is outlined in lesson plan. The materials in lesson plan are related to the daily activities of health and clean living behavior of students. The implementation of based health learning is developed through thematic learning about individual, family, environment, experience, hobby, clean and health. Second, the school health program activities at SDN Magelang 6 are done relevant to the work program based on School Health Program triad, in which one of it is health education. The existence of School Health Program gives much assistant to school in implementing healthbased learning. School Health Program has a responsibility to provide health education to all school members. Health education in primary school can be done in the form of curricular activities that are part of school curriculum. The existence of School Health Program in school has a role to maintain the healthy school environment. The School Health Program has complete facilities such as medical equipment, bed, first aid box, bin, broom, mop, and props which are used by School Health Program staffs when doing health education.